EU Social Inclusion Policies in Post-Socialist Countries Top-Down and Bottom-Up Perspectives on Implementation - Fylling, Ingrid; Baciu , Elena-Loreni; Paulsen Breimo, Janne (Studies in European Sociology, 2020)
This book explores experiences with inclusion policy implementation in seven different post-socialist EU countries. It focuses particularly on two groups of people in constant danger of social exclusion: People with Roma background and people with disabilities.